2022
DOI: 10.1002/adfm.202112151
|View full text |Cite
|
Sign up to set email alerts
|

Harmonizing Graphene Laminate Spacing and Zinc‐Ion Solvated Structure toward Efficient Compact Capacitive Charge Storage

Abstract: Aqueous Zn-ion hybrid capacitors (ZIHCs) present prominent potentials in flexible wearable electronics application scenarios due to their inherent high safety and low cost. Simultaneously, volumetric energy density is one of the crucial parameters to determine the lifespan of the wearable electronics, in which lightweight and miniaturization is a cardinal prerequisite for realistic application. In this work, an aqueous ZIHC is constructed by harmonizing interlayer spacing of the laminate graphene film and Zn-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 84 publications
0
28
0
Order By: Relevance
“…10(d)). 151 Pandey et al designed a dual-function supercapacitor-based energy-storing carbon fiber-reinforced polymeric composite (e-CFRP) for the body panel in an electric vehicle, which can not only store electrical energy but also function as the structural component for the electric vehicle's body shell. This is made possible by using a unique vertically attached graphene on carbon fiber structure electrodes, which plays an important role in improving the energy density because of the enhanced surface area.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…10(d)). 151 Pandey et al designed a dual-function supercapacitor-based energy-storing carbon fiber-reinforced polymeric composite (e-CFRP) for the body panel in an electric vehicle, which can not only store electrical energy but also function as the structural component for the electric vehicle's body shell. This is made possible by using a unique vertically attached graphene on carbon fiber structure electrodes, which plays an important role in improving the energy density because of the enhanced surface area.…”
Section: Reviewmentioning
confidence: 99%
“…The various composites for flexible solid-state electrodes used in the FSHSCs are listed in Table 1. 85,[138][139][140][141][142][144][145][146][149][150][151][152]155,[159][160][161][162][163][164][165][166][167][168][169] Although different yarn-and sheet-type FSHSCs described above have expanded our portfolio of these devices for wearable devices, the interdigitated micro-structure FSHSCs will become the EES of the future miniaturized, flexible, and wearable electronic devices. These are discussed in detail in the next section.…”
Section: Reviewmentioning
confidence: 99%
“…The structure of the Zn‐ion solvation was modified by the addition of ZnCl 2 electrolyte salt to accommodate the controlled laminar ionic transport channels. [ 117 ] As shown in Figure 10h,i, the assembled ZHSCs using ZnCl 2 electrolytes exhibited higher volumetric and rate capacitance, and fast ion diffusion kinetics, compared to these using Zn(Ac) 2 , ZnSO 4 , and Zn(CF 3 SO 3 ) 2 salts. Overall, the experimental findings and computational results demonstrated that the solvation structure of the novel ZnCl 2 electrolyte might significantly increase zinc ion accessibility.…”
Section: Electrolyte Optimizationmentioning
confidence: 99%
“…The salt concentration and anion type have been proved to have a close relationship with zinc deposition and stripping efficiency. [113][114][115][116][117] Wu et al [113] used 3 M Zn (CF 3 SO 3 ) 2 electrolyte to balance the trade-off between cycling stability and energy density with high Zn stripping/plating efficiency (Figure 10a, b). When the F I G U R E 10 (a, b) Schematic illustration of the discharging and charging mechanism of the designed zinc-ion hybrid supercapacitors (ZHSCs).…”
Section: Electrolyte Saltsmentioning
confidence: 99%
See 1 more Smart Citation